Review of Pancreatic Lesions in Von Hippel-Lindau Disease - Tárcia Nogueira Ferreira Gomes; Lívia de Almeida Costa; Luciano Lenz; Giovana Biasia de Sousa; Ermelindo Della Libera; Frank Shigueo Nakao (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Von Hippel-Lindaudisease (VHLD) is a rare hereditary tumor syndrome, inherited in autosomal dominant manner. Patients diagnosed with VHLD have a high risk of developing neoplasms of various organs (eyes, central nervous system, bone, kidney, adrenal glands, epididymis, broad ligament and pancreas). Due to its rarity, most of the physicians fail to properly diagnose it in time, and they might expose patients to a risk of unnecessary surgeries with important consequences in a long run. When this condition is diagnosed, lifelong follow-up is necessary. Pancreatic involvement it is seen in most patients with VHLD and various pancreatic lesions have been described, including cystic lesions (simple unilocular or serous microcystic or macro/micro-cystic adenomas), neuroendocrine tumors (NET), renal cell cancer metastasis and adenocarcinoma. These lesions are rarely the primary presenting tumor and frequently diagnosed during the screening of family members with VHLD, by imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT). Cystic lesions are the most common, generally asymptomatic and are rarely associated with malignant degeneration, except mucinous cysts. It is recommended follow-up and intervention if these lesions become symptomatic or mucinous aspect. NET are usually multiple, nonfunctional and have malignant potential. The management of NET depends on size, doubling time and underlying genetics. Because of their malignant potential, it is necessary careful observation in a long-term  follow-up. If treatment is necessary, more conservative management is preferable. Molecular targets for treatment of NET in VHLD have also been proposed and some drugs are in preclinical or clinical trials.